Multiobjective optimization of the reactive power compensation in electric distribution systems (2014)
Different methods of optimization have been used for the selection and localization of capacitor banks in distribution circuits. However, it is necessary to consider the distortion taken place by the harmonics of the no-linear loads and the possible appearance of resonances between the inductive elements of the system and the existent capacitor banks. On the other hand, it has not been integrated in a single methodology the use of capacitor banks and of passive harmonic filters to compensate the reactive power in harmonic polluted distribution systems. The present work intends as objective to develop this methodology. The developed program is based on the multiobjective optimization algorithm NSGA-II that it is proven with success in several examples.